2023
DOI: 10.3390/en16217313
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bread Bakery Waste as a Binder Additive in the Production of Fuel Pellets from Straw

Sławomir Obidziński,
Paweł Cwalina,
Małgorzata Kowczyk-Sadowy
et al.

Abstract: The paper presents the results of a study on the effects of the addition of bread bakery waste (stale bread, sometimes infected with mold, from store returns) to agricultural waste consisting of triticale straw on the process of solid biofuel pelleting and the physical and fuel properties of the obtained pellets. The pelleting process was conducted in a pelletizer equipped with a flat matrix, with holes 6 mm in diameter, and two pelleting rollers (for straw alone and for a mixture of straw and bread waste with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
5
3
0
Order By: Relevance
“…Although the differences were statistically significant, they were not large from the practical perspective. The moisture content of triticale straw, as determined in a different study (12.6%) [34], was comparable with the findings of this study for straw of cereals harvested in the summer. Gradziuk et al found that the moisture content of rye straw (12.8%) was also similar, whereas that of wheat straw was higher (15.5%), and that of rapeseed (12.6%) and corn straw (19.6%) were lower [17].…”
Section: Thermophysical Characteristicssupporting
confidence: 89%
See 2 more Smart Citations
“…Although the differences were statistically significant, they were not large from the practical perspective. The moisture content of triticale straw, as determined in a different study (12.6%) [34], was comparable with the findings of this study for straw of cereals harvested in the summer. Gradziuk et al found that the moisture content of rye straw (12.8%) was also similar, whereas that of wheat straw was higher (15.5%), and that of rapeseed (12.6%) and corn straw (19.6%) were lower [17].…”
Section: Thermophysical Characteristicssupporting
confidence: 89%
“…A similar ash content of oat straw (5.0% DM) and of corn straw (4.2% DM) to the ash content determined in the current study was found by Szufa et al [40]. On the other hand, the ash contents of triticale straw (4.77% DM) [34] and wheat straw (6.34% DM) [41] were higher than in the findings of the current study for these straw types. A,B,C homogenous groups for the harvest year separately for each attribute; a,b,c,d,e,f homogenous groups for the straw type and harvest year interaction separately for each attribute; no letters denote no significant differences; ± standard deviation.…”
Section: Thermophysical Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…The calorific value and the heat of combustion were determined pursuant to PN-EN ISO 1928:2002 and the methodology described previously in publications [28,29].…”
Section: Determination Of Calorific Value and Heat Of Combustionmentioning
confidence: 99%
“…The latter is a promising crop and, with its rational use, can be a valuable compound feed ingredient and successfully partially replace the cereal crops traditionally used [17,[23][24][25][26][27][28][29][30][31]. This becomes especially important in connection with the growing share of cereals that will be used for the production of biofuels, i.e., ethanol, biodiesel, and solid fuel pellets (e.g., [32][33][34][35]). The purpose of this review is to consider the nutritional, economic, and environmental benefits (as well as the drawbacks) of the rye-wheat hybrid triticale in poultry production.…”
Section: Introductionmentioning
confidence: 99%